Who Benefits from Universal Child Care? Estimating Marginal Returns to Early Child Care Attendance - Cornelissen, Thomas; Dustmann, Christian; Raute, Anna; Schönberg, Uta (Journal of Political Economy, 2018)
We examine heterogeneous treatment effects of a universal child care program in Germany by exploiting variation in attendance caused by a reform that led to a large expansion staggered across municipalities. Drawing on novel administrative data from the full population of compulsory school entry examinations, we find that children with lower (observed and unobserved) gains are more likely to select into child care than children with higher gains. Children from disadvantaged backgrounds are less likely to attend child care than children from advantaged backgrounds but have larger treatment effects because of their worse outcome when not enrolled in child care.